Frontotemporal dementia and neuropsychology: the value of missing values. Issue 6 (1st June 2000) - Smeding, Harriet M M; de Koning, Inge
Abstract : OBJECTIVE: To investigate the effect of missing values due to behavioural disturbances on the neuropsychological test profile in frontotemporal dementia (FTD). The neuropsychological examination of patients with FTD poses a methodological problem. In many patients it is impossible to administer a complete test battery, due to behavioural disturbances inherent to the disease. This study describes the test behaviour of patients with FTD, the number of missing values due to disturbed test behaviour, and its influence on neuropsychological test results. METHODS: Thirty one patients with probable FTD were administered a neuropsychological test battery including measures of memory, intelligence, and executive functioning. Moreover, patients were rated on a global deterioration scale and a test behaviour scale, constructed for this study. RESULTS: The more disturbing the test behaviour, the less tests were assessable, leading to many missing values. The most disturbing features were "positive symptoms" of FTD, such as perseveration and stimulus boundedness. The effect of test behaviour was largest for tests measuring executive functions and reasoning capabilities. The replacement of the missing values due to behavioural disturbances by the lowest score also showed the largest effect on tests of executive function and reasoning abilities. CONCLUSION: Data imputation of missing values due to test behaviour disturbances provides a more differentiated picture of cognitive deficits in FTD.